2020
DOI: 10.1186/s13028-020-00549-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of canine C-reactive protein assays

Abstract: C-reactive protein (CRP), which is released during tissue damage and inflammation, is a useful nonspecific inflammatory marker in both human and veterinary clinical practice. Veterinarians have often used human CRP assays to analyze samples from canine patients, but cross-reactivities between the species affect assay sensitivity and reliability, leading to inaccurate inflammation assessment. To improve the efficiency of inflammation assessment, we developed a canine CRP detection enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“… 29 , 32 The ELISA developed by Waritani et al was shown to have an intraassay CV between 0.7% and 10.0% and an interassay CV between 6.0% and 9.0%. 38 When spiked with purified canine CRP, this assay also demonstrated a recovery between 105% and 109%. 38 Given these performance parameters and the assay's good correlation with the previously validated Laser CRP‐2, 34 it appears sufficiently accurate for clinical use.…”
Section: Measurement Of Canine Crpmentioning
confidence: 92%
See 4 more Smart Citations
“… 29 , 32 The ELISA developed by Waritani et al was shown to have an intraassay CV between 0.7% and 10.0% and an interassay CV between 6.0% and 9.0%. 38 When spiked with purified canine CRP, this assay also demonstrated a recovery between 105% and 109%. 38 Given these performance parameters and the assay's good correlation with the previously validated Laser CRP‐2, 34 it appears sufficiently accurate for clinical use.…”
Section: Measurement Of Canine Crpmentioning
confidence: 92%
“… 38 When spiked with purified canine CRP, this assay also demonstrated a recovery between 105% and 109%. 38 Given these performance parameters and the assay's good correlation with the previously validated Laser CRP‐2, 34 it appears sufficiently accurate for clinical use. To the authors’ knowledge, clinical validation of this assay has not yet been reported in the primary literature.…”
Section: Measurement Of Canine Crpmentioning
confidence: 92%
See 3 more Smart Citations